HDL Levels as a Novel Predictor of Long-Term Adverse Outcomes in Patients with Heart Failure: A Retrospective Cohort Study - Abudouwayiti A; Yisimayili S; Tuersun R; Aimaier S; Yisha D; Zhang XY; Zheng YY; Mahemuti A (Dove Medical Press, 2024)
Aihaidan Abudouwayiti, Sureya Yisimayili, Ruzeguli Tuersun, Salamaiti Aimaier, Didaer Yisha, Xing Yan Zhang, Ying-Ying Zheng,* Ailiman Mahemuti* The First Affiliated Hospital of Xinjiang Medical University, Urumqi, Xinjiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Ying-Ying Zheng; Ailiman Mahemuti, Cardiovascular Department of The First Affiliated Hospital of Xinjiang Medical University, 137 Carp Road, Xinshi District, Urumqi, 830054, Xinjiang, People's Republic of China, Tel +86-15214804944 ; +86-13639970300, Email zhengying527@163.com; xinjiangailiman@163.comBackground: The role of high-density lipoprotein cholesterol (HDL-C) in heart failure (HF) outcomes is contentious. We aimed to assess HDL-C's prognostic value in HF patients.Methods: In this retrospective cohort study (2012- 2022) at the First Affiliated Hospital of Xinjiang Medical University, we analyzed 4442 patients, categorized by HDL-C quartiles. We applied the Cox proportional hazards model to assess survival and report hazard ratios (HR) with 95% confidence intervals (CI).Results: Over a decade, we recorded 1354 fatalities (42.3%) and 820 readmissions. The third HDL-C quartile (0.93- 1.14 mmol/L) showed the lowest mortality rates, with reduced risks in the second and third quartiles compared to the first (Q2 HR=0.809, 95% CI 0.590- 1.109; Q3 HR=0.794, 95% CI 0.564- 1.118). The fourth quartile presented a lower mortality risk compared to the first (Q4 HR=0.887, 95% CI 0.693- 1.134). A significant correlation existed between HDL-C levels and cardiovascular risk (HR=0.85, 95% CI 0.75- 0.96, p< 0.01).Conclusion: HDL-C levels exhibit a complex association with mortality in HF, indicating the importance of HDL-C in HF prognosis and the need for tailored management strategies.Keywords: high-density lipoprotein cholesterol, heart failure, death, readmission, cardiovascular disease